MOTIVASI PEMBELAARAN DALAM PERSPEKTIF HADITS LEARNING MOTIVATION IN THE HADITH PERSPECTIVE - Poniam Poniam (CV. Adiba Aisha Amira, 2023)
Islam requires its followers to seek knowledge. In connection with this obligation, there are many Hadiths of the Prophet Muhammad SAW, both implicit and explicit, that motivate Muslims to always learn and seek knowledge without distinguishing between religious knowledge and general knowledge. This motivation can be extrinsic or intrinsic. Extrinsic motivation by stating several virtues of learning or seeking knowledge, such as those who study, will have an easier path to heaven, their rank will be elevated and so on. Meanwhile, intrinsic motivation means that learning must be based on a sincere intention to gain Allah's approval. Learning motivation according to this hadith also differentiates learning motivation according to Islam from learning theories according to Western learning theories which are secular and anthropocentric. The concept of learning motivation in Islam is transcendental and theocentric which places humans in a position of balance, that learning is not only for the benefit of the world, but knowledge that increases faith and obedience to Allah and His Messenger, as well as being beneficial not only for worldly life, but also for the afterlife.